Trends in antenatal care attendance and health facility delivery following community and health facility systems strengthening interventions in Northern Uganda - Ediau, Michael (BioMed Central, 2013)
BACKGROUND: Maternal morbidity and mortality remains high in Uganda; largely due to inadequate antenatal care (ANC), low skilled deliveries and poor quality of other maternal health services. In order to address both the demand and quality of ANC and skilled deliveries, we introduced community mobilization and health facility capacity strengthening interventions. METHODS: Interventions were introduced between January 2010 and September 2011. These included: training health workers, provision of medical supplies, community mobilization using village health teams, music dance and drama groups and male partner access clubs. These activities were implemented at Kitgum Matidi health center III and its catchment area. Routinely collected health facility data on selected outcomes in the year preceding the interventions and after 21 months of implementation of the interventions was reviewed. Trend analysis was performed using excel and statistical significance testing was performed using EPINFO StatCal option. RESULTS: The number of pregnant women attending the first ANC visit significantly increased from 114 to 150 in the first and fourth quarter of 2010 (OR 1.72; 95% CI 1.39–2.12) and to 202 in the third quarter of 2011(OR 11.41; 95% CI 7.97–16.34). The number of pregnant women counselled, tested and given results for HIV during the first ANC attendance significantly rose from 92 (80.7%) to 146 (97.3%) in the first and fourth quarter of 2010 and then to 201 (99.5%) in the third quarter of 2011. The number of male partners counseled, tested and given results together with their wives at first ANC visit rose from 13 (16.7%) in the fourth quarter of 2009 to 130 (89%) in the fourth quarter of 2010 and to 180 (89.6%) in the third quarter of 2011. There was a significant rise in the number of pregnant women delivering in the health facility with provision of mama-kits (delivery kits), from 74 (55.2%) to 149 (99.3%) in the second and fourth quarter of 2010. CONCLUSIONS: Combined community and facility systems strengthening interventions led to increased first ANC visits by women and their partners, and health facility deliveries. Interventions aimed at increasing uptake of maternal health services should address both the demand and availability of quality services.